2023
DOI: 10.2147/opth.s396781
|View full text |Cite
|
Sign up to set email alerts
|

Terson Syndrome – Clinical Presentation, Management, and Visual Outcomes in a Tertiary Centre

Abstract: Purpose The purpose of this study was to characterize the clinical presentation, management strategy and visual outcomes of patients diagnosed with Terson syndrome and followed in a tertiary centre in Portugal. Patients and Methods A single-centre retrospective study was performed, based on the survey review of the medical records of every consecutive patient diagnosed with Terson syndrome and followed from January 2018 to August 2021. The change in best-corrected visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…This is attributed to the fact that routine ophthalmologic examinations are not consistently conducted, and some patients are unable to communicate their visual complaints due to their underlying medical conditions. This assertion is corroborated by a study conducted by Lima-Fontes et al [8] in 2023, wherein the authors underscored that the diagnosis of Terson's syndrome commonly encounters delays. This delay is attributed to the concurrent presence of neurological deficits and a compromised conscious state in affected individuals.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…This is attributed to the fact that routine ophthalmologic examinations are not consistently conducted, and some patients are unable to communicate their visual complaints due to their underlying medical conditions. This assertion is corroborated by a study conducted by Lima-Fontes et al [8] in 2023, wherein the authors underscored that the diagnosis of Terson's syndrome commonly encounters delays. This delay is attributed to the concurrent presence of neurological deficits and a compromised conscious state in affected individuals.…”
Section: Introductionmentioning
confidence: 63%
“…The incidence of Terson's syndrome varies from 8% to 46% as a result of differences in the diagnostic method. The frequency of Terson's syndrome is relatively high and yet 77% of such cases are overlooked in daily reports [ [8] , [9] , [10] ]. In a systematic review of 154 scholarly works on the incidence of Terson's syndrome, McCarron et al [11] reported a 13% frequency among patients studied prospectively and 3% studied retrospectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that delays in identifying Terson syndrome can result in poorer visual outcomes and associated morbidity. Patients with Terson syndrome who are not adequately managed are at risk of developing perimacular folds, retinal detachment, and ghost cell glaucoma 9 .…”
Section: Case Discussionmentioning
confidence: 99%
“…The management options of sub-ILM hemorrhage can vary depending on multiple parameters, such as the general condition of the patient, visual acuity, bilaterality, location, severity of the hemorrhage, and time since its onset, associated ocular pathology [ 3 , 5 ]. Treatment options could include observation, YAG laser hyaloidotomy, or pars plana vitrectomy with ILM peeling and aspiration of the underlying hemorrhage [ 5 , 6 ]. In most cases of TS, spontaneous recovery is expected, and therefore, conservative treatment is usually opted for [ 1 ].…”
Section: Discussionmentioning
confidence: 99%